Liuweizhiji Gegen-Sangshen beverage protects against alcoholic liver disease in mice through the gut microbiota mediated SCFAs/GPR43/GLP-1 pathway - Tang, Mingyun; Zhao, Long; Huang, Fuchun; Wang, Tiangang; Wu, Xu; Chen, Shanshan; Fu, Juan; Jiang, Chaoli; Wei, Shulin; Zeng, Xuseng; Zhang, Xiaoling; Zhou, Xin; et al. (Frontiers in Nutrition, 2024)
IntroductionAlcoholic liver disease (ALD) is a pathological state of the liver caused by longterm alcohol consumption. Recent studies have shown that the modulation of the gut microbiota and its metabolic products, specifically the short-chain fatty acids (SCFAs), exert a critical role in the evolution and progression of ALD. The Liuweizhiji Gegen-Sangshen beverage (LGS), as a functional beverage in China, is derived from a traditional Chinese herbal formula and has been clinically applied for ALD treatment, demonstrating significant efficacy. However, the underlying mechanisms of LGS for alleviating ALD involving gut microbiota regulation remain unknown.MethodsIn this study, an ALD murine model based on the National Institute on Alcohol Abuse and Alcoholism (NIAAA) method was established.ResultsThe results showed that oral LGS treatment dose-dependently alleviated alcoholinduced liver injury and inflammation in mice through decreasing levels of ALT, AST and proinflammatory cytokines (TNF-α, IL-6, IL-1β). LGS significantly improved liver steatosis, enhanced activities of alcohol metabolizing enzymes (ALDH and ADH), and reduced the CYP2E1 activity. Notably, regarding most detected indices, the effect of LGS (particularly at medium and high dose) was comparable to the positive drug MTDX. Moreover, LGS had a favorable effect on maintaining intestinal barrier function through reducing epithelial injury and increasing expression of occludin. 16S rRNA sequencing results showed that LGS remarkably modulated gut microbiota structure in ALD mice via recovering alcohol-induced microbial changes and specifically mediating enrichment of several bacterial genera (Alloprevotella, Monoglobus, Erysipelatoclostridium Parasutterella, Harryflintia and unclassified_c_Clostridia). Further study revealed that LGS increased production of SCFAs of hexanoic acid in cecum, promoted alcohol-mediated reduction of GRP43 expression in ileum, and increased serum GLP-1 level.DiscussionOverall, LGS exerts a remarkable protective effect on ALD mice through the gut microbiota mediated specific hexanoic acid production and GPR43/GLP-1 pathway.